THE ANALYSIS OF ED SHEERAN SONGS TO IMPROVE STUDENT’S LISTENING SKILL - Bella Nurinsani; Rida Nurul Manilah; Anita Anggareni (IKIP Siliwangi, 2018)
This Study entitled “The Analysis of Ed Sheeran Songs to Improve Student’s Listening Skill”. The research was aimed to find out improved student’s listening skill ability. Wheather Ed Sheeran songs was founding increase student’s listening skill, because Ed Sheeran is a singer from England (UK) and his dialect of English is British English, so we were learning British English from the Ed Sheeran songs. In addition, Ed Sheeran was preferred many people in the world. People in the world had been understanding a lesson if a lesson had found for them, and we can’t deny if people in the world like songs and music. A song is the sound of art tone in the order, combination and the temporal relationship usually with accompanied by a musical instrument, the produce the music that has unity and continuity. The approach of this research is qualitative.